Mathematical and simulation model for determining the technical and economic efficiency of the implementation and use of agricultural waste conversion technology into biogas according to the seasons of the year - Zablodsky, M.; Shvorov, S.; Polishchuk, V.; Trokhaniak, V.; Valiev, T. (Energy and Automation, 2024)
The purpose of the article is to develop the methodological principles of creating a mathematical and simulation model of the process of functioning of a methane tank to determine the technical and economic efficiency of the implementation and use of the technology of converting agricultural waste into biogas. The mathematical model is a system of differential equations describing the change in the fermenter of substrate nutrient concentrations, methanogen biomass, and the dynamics of biogas output. The system of differential equations is solved in the Simulink package. An example of the application of the developed models for forecasting biogas output during methane monofermentation of cow manure is given. This approach can be used not only for modeling the process of methane monofermentation of cow manure, but also with the addition of seasonal agricultural waste to intensify biogas output. Since the use of vegetable agricultural waste is seasonal, the developed models can be used to predict the output of purified biogas for its injection into the gas transportation or gas distribution system in the summer at different initial values of the biomass concentration of methanogens, the concentration of nutrients in the substrate, and the volume of the fermenter. In the cool period of the year, these volumes of biomethane can be used for cooking, heating residential buildings and premises of the united territorial community. Key words: biogas, biogas plant, fermenter, mathematical and simulation model, methanogens